Ambulatory Orchidopexy Is a Potential Solution to Improve the Rate of Timely Repair in Cryptorchid Boys: An 8 Year Retrospective Study of 4,972 Cases - Zhao, Tianxin; Deng, Fuming; Jia, Wei; Gao, Xiaofeng; Li, Zhongmin; Tang, Xiangliang; Li, Dian; Zhou, Rui; Shu, Fangpeng; Zhang, Jin; Zhang, Zhengtao; Fu, Wen; et al. (Frontiers in Pediatrics, 2021)
Background: Cryptorchidism is the most common congenital anomaly in pediatric urology. Although early surgery on cryptorchid boys is recommended by pediatric urologists worldwide, the actual age at orchidopexy is often older than the recommended age. Our medical center has started performing ambulatory orchidopexy since March 2016 at the ambulatory surgery center. We aimed to investigate whether ambulatory orchidopexy can improve the timely repair rate. Methods: A retrospective analysis was conducted from 2012 to 2019 at our medical center. Ambulatory orchidopexy was started at our medical center on March 24, 2016. Boys born on or after September 24, 2015 were classified into the "with ambulatory medical resource" group, and boys born before September 24, 2014, were classified into the "without ambulatory medical resource" group. The timely repair rates were calculated and compared. Results: A total of 4,972 cryptorchidism cases were included in the final study. Approximately 33.0% of cryptorchid boys received timely surgery (orchidopexy by the age of 18 months), and only 6.8% of all cryptorchid boys underwent surgery before the age of 1 year. After the performance of ambulatory orchidopexy, the timely repair rate increased from 25.7% to 37.0% (P < 0.001), and the percentage of patients receiving surgery before the age of 1 year increased significantly from 3.5% to 8.6% (P < 0.001). The proportion of timely repair in patients with ambulatory medical resources was significantly higher than that in patients without ambulatory medical resources (15.6% vs 58.2%, P < 0.001). Significant changes in the rate of surgery before 12 months of age were also found between the two groups (2.4% vs 14.8%, P < 0.001). Conclusions: After the performance of ambulatory orchidopexy in our medical center, the rates of both timely repair and receiving surgery before the age of 1 year increased significantly. Ambulatory orchidopexy is a potential solution to improve the rate of timely repair in cryptorchid boys, and it is worthy of promotion in developing countries and regions.